Investigating cumulative effects of pre-performance routine interventions in beach volleyball serving - Wergin, V. V.; Beckmann, J.; Gröpel, P.; Mesagno, C. (PLOS ONE, 2020)
Pre-performance routines (PPRs) can be used in certain sports to minimize the effects of choking under pressure. This study aimed to investigate the cumulative effectiveness of PPR interventions on the accuracy of beach volleyball serves. Fifty-four beach volleyball players were randomly assigned to one of three PPR intervention groups or a control group. Participants performed 10 serves at a target on the opposite side of the beach volleyball court (pretest), were educated on a PPR intervention, and then completed 10 serves at the target under pressure that was induced through videotaping and ego-relevant instructions (posttest). The results indicated no difference in post-test serving accuracy among the intervention groups and the wait-list control group and no difference in effectiveness between cumulative and isolated PPR use. A possible explanation may be the inefficiency of the pressure manipulation. However, the null results related to isolated and cumulative PPR use under general (i.e., no pressure) conditions are still an important research finding. Future research should investigate the effectiveness of cumulative and other PPRs in other sports in general and under pressure.